PENGARUH SUHU SINTERING TERHADAP SIFAT MEKANIK KERAMIK BERBAHAN LEMPUNG DAN ABU SEKAM PADI - Husain, sadang; Haryanti, Ninis Hadi; Manik, Tetti Novalina (Jurnal Fisika FLUX, 2016)
Abstract. Study about the influence of sintering temperature on mechanical properties of ceramics has been done using clay and rice husk ash. Limitation of mechanical properties tested is the comppressive strength. This is done in order to determine the effect of variation of sintering temperature to compressive strength of ceramic with clay and rice husk ash. In addition, the calculation of fuel density and shrinkage also performed in this study. Variation in the composition of clay and rice husk ash is made to see the maximum composition of these materials. The result shows that the density of the ceramic material on the composition of clay and rice husk ash volume 100: 0, 90:10, 80:20, 70:30, 60:40, and 50:50 are 2.14; 2.01; 1.98; 1.88; 1.84; and 1.78 g / cm3 respectively. Shrinkage of ceramic material has ranges between 3.4% -11.4%. The value of maximum compressive strength of clay and rice husk ash ceramic at 7000C, 8000C, and 9000C sintering temperature are 115.58; 115.58, and 128.42 kg / cm3. This value conforms the standard if used for bricks. The greater the sintering temperature, the higher the compressive strength of the ceramic. The best composition of clay and rice husk ash is 70:30. This ceramic can be used as building material, especially in the swampy area because it has a lighter weight. Keywords: Ceramics, Clay, Rich husk ash, comppressive strength